15. REZIM INTERNASIONAL SEBAGAI INSTRUMEN KEPENTINGAN NASIONAL: KEBIJAKAN RUSIA BERGABUNG DALAM UN GLOBAL COUNTER-TERRORISM STRATEGY 2006 - Rakha Dwi Hadianto; Reni Windiani; Mohammad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Relations between Russia and America had been established for 209 years, started from1807. Relations between Russia and America most filled with disharmony rather thanharmony. Rivality on two states was seen on the Cold War. The bipolar phenomenon doesnot only happen for politic gain in blocs of nations between Russia and America, but mostlikely a refection to some characteristic of nation. This reasearch will explain why Russiajoin UN Global Counter-Terrorism Strategy that known as respond to 9/11. Using rationalchoice theory, this research was found that Russia puts forward the principle of rational toface the threat of terrorist groups in their country. In needs to know the movement ofinternational network from Basayev group, make Russia participate in the global counterterrorismregime formed by the United Nations. Some adjustments shown that the FederalLaw No.35-Fz had replace the Federal Law 130-Fz 1998 before as a counter-terrorism lawsince 2006. The changes of strategy does not only reflect the rationality of an actor, butalso sovereignity of a state.